2016
DOI: 10.1136/archdischild-2015-309525
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for advanced resuscitation in term and near-term infants: a case–control study

Abstract: We identified 10 risk factors significantly associated with the need for ANR in newborns ≥34 weeks. We developed a validated risk score that allows the identification of newborns at higher risk of need for ANR. Using this tool, the presence of specialised personnel in the delivery room may be designated more appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
2
12
0
2
Order By: Relevance
“…However, published reports do not show any association between magnesium sulfate exposure and level of delivery room resuscitation in the neonates (23,24). The association between SGA status and all levels of resuscitation except CPR in MPT infants in our study is consistent with previously reported data in late preterm infants (4,6,20). Maternal hypertension is an important risk factor for preterm delivery and SGA status, which could lead to emergency Cesarean section and use of antepartum magnesium sulfate (25).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, published reports do not show any association between magnesium sulfate exposure and level of delivery room resuscitation in the neonates (23,24). The association between SGA status and all levels of resuscitation except CPR in MPT infants in our study is consistent with previously reported data in late preterm infants (4,6,20). Maternal hypertension is an important risk factor for preterm delivery and SGA status, which could lead to emergency Cesarean section and use of antepartum magnesium sulfate (25).…”
Section: Discussionsupporting
confidence: 93%
“…Aziz et al reported a 2-fold increase in respiratory support (positive pressure ventilation- endotracheal intubation) among moderate-high risk infants born to mothers with hypertension during pregnancy across all GAs (5). Similar associations have been reported between pregnancy induced hypertension and advanced resuscitation (endotracheal intubation and CPR) in infants greater than 34 weeks GA (6), and maternal hypertension and bag and mask ventilation in late preterm infants (4). Maternal hypertension was a significant risk factor among extremely low birth weight infants receiving CPR in the delivery room (8).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…En un estudio reciente, Berazategui y colaboradores identificaron factores de riesgo significativamente asociados con la necesidad d e r e a n i m a c i ó n n e o n a t a l a v a n z a d a e n RN ≥ 34 semanas. 11 Los autores desarrollaron un puntaje de riesgo validado que permitía la identificación de RN con mayor riesgo. La utilización de esta herramienta puede permitir convocar la presencia de personal especializado en la sala de partos de manera más adecuada.…”
Section: Anticipaciónunclassified